TEACHING AND LEARNING GRAMMAR AND STYLE IN WRITING - A PRACTICAL APPROACH - Larcy C Abello (Celt: A Journal of Culture, English Language Teaching & Literature, 2015)
This report focuses on the exploration of the three dimensions of grammarform, meaning, and usea practical approach to teach and learn grammar and style and effect communication. Using journalistic, literary, and academic/scientific/technical texts, this describes the teaching-learning process involved in language activities, such as text analysis, text conversion, and writing" of original texts. This paper, explains how the procedure engages students in meaningful tasks that hone their language skills and enhance their writing ability and could inspire them to speak and communicate ideas, applying critical/analytic thinking even outside the classroom thus developing autonomous learners. This demonstrates a practical approach to the teaching of language as communication based on a careful consideration of the nature of language and of the strategic development of writing skills among learners within a supportive social context.